The influence of work ethic, work discipline, and work stress on the performance of employees of the East Jakarta City Administration Secretariat - Bayu Sukma Wisesajati; Renny Husniati (ProBisnis : Jurnal Manajemen, 2023)
This research’s purpose is to determine and prove the influence of self-efficacy, organizational justice, and perceived organizational support on organizational citizenship behavior. This research analyzes 48 staff in Secretariat of the Administration City of East Jakarta as a sample, with a sampling technique using a Probability Sampling technique and Simple Random Sampling by spin-wheels. The SEM based PLS is chosen as data analysis technique in this study. The results of the study shows that (1) Work Ethic has a positive and significant effect on Employee Performance in the Secretariat of the Administration City of East Jakarta, (2) Work Discipline has a positive and significant effect on Employee Performance in the Secretariat of the Administration City of East Jakarta, (3) Work Stress has a positive and significant effect on Employee Performance in the Secretariat of the Administration City of East Jakarta.